# lect6 - Prove or disprove the following proposition For any...

This preview shows pages 1–10. Sign up to view the full content.

1 For any three sets A, B and C ( A B ) C = A ( B C ) Prove or disprove the following proposition To disprove that the proposition is true for any sets its sufficient to find a single example of three sets, such that the proposition is false. First you need to decide what to do…If the proposition looks like to be true, prove it for arbitrary sets. But suppose you suspect that it not always true… It is sufficient to find a single counterexample to disprove it!

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
2 A B C A B ( A B ) C = A ( B C ) ? B C A B C ( A B ) C A B C A ( B C ) A B C
3 We are going to disprove by counterexample . A = {1, 2, 3, 4} B = {1, 3, 5, 6} C = {1, 2, 5, 7} A B C 1 3 4 2 5 7 6 ( A B ) C = A ( B C ) A B = {1, 3}, ( A B ) C = {1, 2, 3, 5, 7} B C = {1, 2, 3, 5, 6, 7}, A ( B C ) = {1, 2, 3}

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
4 You can use a membership method here. A B C A B ( A B ) C B C A ( B C ) 1 1 1 1 1 1 1 1 2 1 1 0 1 1 1 1 3 1 0 1 0 1 1 1 4 1 0 0 0 0 0 0 5 0 1 1 0 1 1 0 6 0 1 0 0 0 1 0 7 0 0 1 0 1 1 0 8 0 0 0 0 0 0 0
5 Theorem 5. Let A , B and C be arbitrary sets. Prove that if A B = C B and A B = C B, then A = C . What this theorem says? A B = C B A = C / / A B = C B A = C But A B = C B and A B = C B A = C Counterexample: A = {1}, C = {1, 2}, B ={1, 2} Counterexample: A = {1}, C = {1, 2}, B ={1}

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
6 A B = C B A C A C
7 A B = C B A C A C

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
8 Direct proof of p q Assume p : A B = C B and A B = C B to prove q: A = C The equality of two sets can be proved as two subset relations (‘double inclusion’ ): A C C A A = C So, there should be two parts of the proof. 1). A B = C B and A B = C B A C 2). A B = C B and A B = C B C A x A x A B x C B x C x B x A B x C B x C
9 Part 1: proof of A C Assume A B = C B (1) and A B = C B (2) .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 24

lect6 - Prove or disprove the following proposition For any...

This preview shows document pages 1 - 10. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online